Advanced lung adenocarcinoma harboring uncommon EGFR 19 Del and T790M/trans-C797S mutations after resistance: a case report and literature review - Xiao, Yuting; Ren, Dunqiang; Bi, Huanhuan; Zhou, Yinxue; Shao, Yanmei; Han, Weizhong; Na, Na; Wang, Hongmei (Frontiers in Oncology, 2025)
The most common epidermal growth factor receptor (EGFR) mutation in non-small cell lung cancer (NSCLC) is exon 19 deletion (19del), which is sensitive to EGFR tyrosine kinase inhibitors (EGFR-TKIs). However, uncommon EGFR 19del mutations exhibit varied responses to EGFR-TKI treatment. Research and clinical data on these uncommon subtypes are limited. Additionally, resistance to EGFR-TKIs is inevitable. EGFR C797S is a frequent mechanism of resistance to third-generation EGFR-TKIs, usually occurs in cis with T790M and in 5% of patients in trans. Here, we report a patient diagnosed with lung adenocarcinoma harboring EGFR 19Del L747-A755delinsSKD mutation with co-occurring T790M and trans-C797S mutations, who showed a positive response to combination therapy with first- and third-generation TKIs. This case report suggests an effective treatment option for such patients.